2020
DOI: 10.1101/2020.03.20.000505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The molecular structure of primary cilia revealed by cryo-electron tomography

Abstract: Primary cilia are microtubule-based organelles involved in key signaling and sensing processes in eukaryotic cells. Unlike motile cilia, which have been thoroughly studied, the structure and the composition of primary cilia remain largely unexplored despite their fundamental role in development and homeostasis. They have for long been falsely regarded as simplified versions of motile cilia because they lack distinctive elements such as dynein arms, radial spokes, and central pair complex. However, revealing th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Although early cross‐sectional electron microscopy studies have challenged the 9 + 0 paradigm of the ciliary axoneme, its three‐dimensional high‐resolution structural map has remained unknown until recently. The application of serial section electron tomography and cryo‐electron microscopy combined 'cryo‐peel‐off' sample preparation method in kidney epithelial cells together revealed unprecedented insight into the near‐native 3D structure of the primary cilia and confirmed that its axonemal organization does not conform to the canonical 9 + 0 configuration [18,19] (Fig. 1B).…”
Section: Structural Complexity Of the Primary Ciliummentioning
confidence: 99%
See 2 more Smart Citations
“…Although early cross‐sectional electron microscopy studies have challenged the 9 + 0 paradigm of the ciliary axoneme, its three‐dimensional high‐resolution structural map has remained unknown until recently. The application of serial section electron tomography and cryo‐electron microscopy combined 'cryo‐peel‐off' sample preparation method in kidney epithelial cells together revealed unprecedented insight into the near‐native 3D structure of the primary cilia and confirmed that its axonemal organization does not conform to the canonical 9 + 0 configuration [18,19] (Fig. 1B).…”
Section: Structural Complexity Of the Primary Ciliummentioning
confidence: 99%
“…In contrast to the periodic localization of the MIPs in the motile cilia axonemes, the MIPs localize sparsely along the axoneme of the primary cilium, which raises questions that pertain to how the stability of the primary cilium is maintained. The identities of the densities identified in the 3D structural maps are not known except for microtubule (+) end‐tracking protein EB1 that decorates the axoneme and actin filament bundles that underlie the ciliary membrane [18]. A recent study identified a helical inner scaffold for the centrioles and showed that it is required for maintaining the structural integrity of the centrioles [26].…”
Section: Structural Complexity Of the Primary Ciliummentioning
confidence: 99%
See 1 more Smart Citation
“…Anterograde train movement to the ciliary tip is powered by kinesin-II (stage 3) [ 12 , 35 , 36 ]. It occurs on the B-tubule of microtubule doublets [ 37 ], and can also occur on the singlet A-tubules found in the distal regions of primary cilia [ [38] , [39] , [40] ]. At the ciliary tip, anterograde trains remodel into retrograde trains (stage 4) [ 28 , 37 , [41] , [42] , [43] , [44] ], which return to the ciliary base by moving along the A-tubule under the power of dynein-2 (stage 5) [ 37 , [45] , [46] , [47] ].…”
Section: Overview Of the Ift Cyclementioning
confidence: 99%
“…The basal body is anchored to the plasma membrane through its distal appendages. Recent electron tomography studies of the cilium generated its 3D structural maps, which significantly changed the widely accepted 9+0 paradigm for the axonemal organization of ciliary microtubules [51,52]. According to the revised model, the nine radially arranged microtubule doublets at the proximal end of the axoneme transitions into an unstructured bundle of microtubule singlets of variable lengths towards the distal end of the cilium.…”
Section: Primary Ciliummentioning
confidence: 99%